Epidemiology of early and late‐onset neonatal sepsis in an Australian regional special care nursery with a high proportion of Aboriginal and Torres Strait Islander births. (3rd June 2022) - Wright, Natalie; Francis, Laura; Bonney, Dennis; Wang, Zhiqiang; Francis, Joshua
Abstract : Aim: To describe the incidence and aetiology of early and late‐onset neonatal sepsis and compare rates in Aboriginal and Torres Strait Islander infants against non‐Indigenous infants in the Top End of the Northern Territory. Methods: This was a retrospective case series of infants with positive blood or cerebrospinal fluid cultures at Royal Darwin Hospital between 2012 and 2016. Cultures from infants during initial hospital admission up to 120 days of age were included for analysis. Demographic, clinical, laboratory and treatment data were collected from medical records. Published definitions of sepsis and criteria for organism pathogenicity and were used to determine cases of sepsis. Results: There were 52 episodes of sepsis in 45 infants. There were eight cases of early onset sepsis, with an incidence of 0.51 per 1000 live births. The incidence was similar for Aboriginal and non‐Indigenous infants. The case fatality rate was 25%. Late‐onset sepsis occurred in 44 cases, comprising 1.3% of all infants admitted to the special care nursery. Coagulase‐negative Staphylococcus was the most frequently cultured organism. Case fatality rate was 11%. Aboriginal and Torres Strait Islander infants had a five‐time higher risk of late‐onset sepsis compared with non‐Indigenous infants; however, their increased risk was not independent of other sepsis risk factors of low rates and prematurity. Conclusions: The incidence of culture‐confirmed early and late‐onset sepsis was low, but case fatality was high. Bacteraemia is an important contributor to neonatal and infant mortality in our setting.